Ethanol‐mediated suppression of IL‐37 licenses alcoholic liver disease. (16th December 2017) - Grabherr, Felix; Grander, Christoph; Adolph, Timon E.; Wieser, Verena; Mayr, Lisa; Enrich, Barbara; Macheiner, Sophie; Sangineto, Moris; Reiter, Andreas; Viveiros, Andre; Zoller, Heinz; Bufler, Philip; et al.
Abstract: Background & Aims: Chronic alcohol consumption and alcoholic liver disease (ALD) afflicts individuals with substantial morbidity and mortality with limited treatment options available. Hepatic inflammation, triggered by activated Kupffer cells, is a driving force in alcoholic liver disease. Interleukin 37 (IL‐37) exerts anti‐inflammatory effects in hepatic diseases, however, the impact of Interleukin 37 on alcoholic liver disease is unknown. In this study, we addressed the role of Interleukin 37 in alcoholic liver disease. Methods: We utilized Interleukin 37 expressing transgenic mice and human recombinant Interleukin 37 in models of alcoholic liver disease. Interleukin 37 expression was measured in liver samples of 20 alcoholic steatohepatitis and 36 non‐alcoholic fatty liver disease patients. Results: Interleukin 37 transgenic mice are not protected against hepatic injury and inflammation in alcoholic liver disease. Ethanol suppressed Interleukin 37 expression in transgenic mice. Alcoholic steatohepatitis (ASH) patients similarly exhibited reduced Interleukin 37 expression when compared to non‐alcoholic fatty liver disease (NAFLD) patients. Human recombinant Interleukin 37 ameliorated hepatic inflammation in a binge drinking model of alcoholic liver disease. Conclusion: We provide evidence for an exogenous noxae that suppresses Interleukin 37 expression which limits its anti‐inflammatory effects in alcoholic liver disease.